ОСОБЕННОСТИ ПОСТРОЕНИЯ ТРЕНИРОВОЧНОГО ПРОЦЕССА В ХУДОЖЕСТВЕННОЙ ГИМНАСТИКЕ - Ахмедова, Д.А. (SCIENCE and SOCIETY, 2020)
In the presented article, the issues of planning, the means of training, the process of developing special-motor readiness, the education of physical qualities among gymnasts of 10-12 years old are considered. It is shown that the inclusion of purposefully selected exercises in the complexes, and in particular choreography exercises, contribute to the successful mastering of the program requirements for the technical training of gymnasts of 10-12 years old.
Keywords: training process; special motor and physical training; choreographic training; control tests; competitions